Urban livelihoods and food and nutrition security in Greater Accra, Ghana - Maxwell, Daniel G.; Levin, Carol E.; Armar-Klemesu, Margaret; Ruel, Marie T.; Morris, Saul Sutkover; Ahiadeke, Clement (International Food Policy Research Institute, 2000)
Accra offers a compelling case study of the contemporary impact of urban life on the livelihoods, food security, and nutritional status of its people. The Accra Urban Food and Nutrition Study was a collaborative effort between IFPRI, the Noguchi Institute of Medical Research, and the World Health Organization to assess the nature of urban poverty and the relationship between urban poverty and food insecurity or malnutrition in Accra, Ghana, in 1996–97. By exploring the major determinants of food security and nutrition status, the study develops indicators of food and livelihood security that are appropriate for an urban setting. The study consists of participatory community studies, household case studies, a household survey carried out in 19 areas of Greater Accra Metropolitan Area, and follow-up interviews and focus groups.